1991
DOI: 10.1037/0021-9010.76.6.810
|View full text |Cite
|
Sign up to set email alerts
|

On the extent and reduction of avoidable absenteeism: An assessment of absence policy provisions.

Abstract: This field study of employees (A' = 1,292) of a public utility company had several objectives: (a) to identify that portion of employee absenteeism that is avoidable; (b) to compare this measure of avoidable absenteeism with more traditional measures, and (c) to examine the relationship of the measure of avoidable absenteeism with a selected absence policy-a waiting-time provision whereby employees were compensated differently for absenteeism. The avoidable absenteeism measure was more robustly related to pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0
6

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 47 publications
3
66
0
6
Order By: Relevance
“…A test±retest coecient of 0.91 over 6 weeks was found using this avoidable absence operationalization for a separate sample. Also the mean self-reported level of 8.1 total absences/year was within the 95 per cent con®dence interval for the 8.5 total absences/year derived from archival sources (Dalton and Mesch, 1991). Dalton and Mesch (1991) found that avoidable absence could be more strongly explained (versus total or unavoidable absence) and that organizational absence policy was a much more powerful predictor than demographic and work attitudes for avoidable absence.…”
Section: Absencementioning
confidence: 97%
See 2 more Smart Citations
“…A test±retest coecient of 0.91 over 6 weeks was found using this avoidable absence operationalization for a separate sample. Also the mean self-reported level of 8.1 total absences/year was within the 95 per cent con®dence interval for the 8.5 total absences/year derived from archival sources (Dalton and Mesch, 1991). Dalton and Mesch (1991) found that avoidable absence could be more strongly explained (versus total or unavoidable absence) and that organizational absence policy was a much more powerful predictor than demographic and work attitudes for avoidable absence.…”
Section: Absencementioning
confidence: 97%
“…An inability to follow either Johns ' (1994) or Steel and Rentsch's (1995) recommendations can hurt the reliability of the data collected. Dalton and Mesch (1991) were able to follow many of these recommendations in operationalizing separate measures of unavoidable (involuntary) and avoidable (voluntary) absence (Chadwick-Jones, Nicholson and Brown, 1982;Driver and Watson, 1989). Unavoidable absence was measured by asking employees to ®ll in`how many days you were o the job in the last year because of your health (colds,¯u, injuries, etc.)?'…”
Section: Absencementioning
confidence: 99%
See 1 more Smart Citation
“…To correct for unreliability in the records-based measures, we used the reliability coefficients from the recent meta-analysis by Johns and Al Hajj (2014) which reported a sample size weighted population reliability of .53 for total time lost, .52 for frequency of absence, and .53 for the combined indexes (K = 95, N = 25,587). To correct for unreliability in the self-reports we conducted an original bare-bones meta-analysis (Hunter & Schmidt, 1990, 2004 of the four testretest self-report absence reliability coefficients identified in our search (Blau, Tatum, & Cook, 2004;Dalton & Mesch, 1991;Laestadius, Ye, & Dimberg, 2008;Tang & Hammontree, 1992).…”
Section: Meta-analytic Proceduresmentioning
confidence: 99%
“…Research on CWB has been done differently, with some research looking at specific facets of CWB such as absence (e.g., Dalton and Mesch, 1991), aggression (e.g., Douglas and Martinko, 2001;Fox and Spector, 1999), and theft (e.g., Greenberg, 1990). At the same time, studies on CWB also looked at these behaviors collectively and this will be explored more below.…”
Section: Introductionmentioning
confidence: 99%